The effect of brand trust, tax socialization, and service quality on individual taxpayer compliance with satisfaction as an intervening variable at the Palembang Ilir Timur Primary Tax Service Office - Rozali, Medy; Natalisa, Diah; Maulana, Ahmad; Widiyanti, Marlina (International journal of business, economics and management, 2025)
This study aims to determine the influence of brand trust, tax socialization, and service quality on individual taxpayer compliance, with satisfaction as an intervening variable at the Palembang Ilir Timur Primary Tax Service Office. A quantitative research method with a causality approach was applied in this study, involving a survey of 100 active taxpayers at the Palembang Ilir Timur Primary Tax Service Office. Data was collected using a Likert scale questionnaire and analyzed using the Structural Equation Model Partial Least Square (SEM-PLS). The results of the study based on direct effects show that tax socialization has a positive and significant effect on individual taxpayer compliance, while brand trust and service quality do not have a significant effect on individual taxpayer compliance. Meanwhile, based on indirect effects, it shows that brand trust, tax socialization, and service quality each have a positive and significant effect on individual taxpayer compliance through satisfaction as an intervening variable. This indicates that satisfaction can mediate the relationship between brand trust, tax socialization, and service quality on individual taxpayer compliance.